2017
DOI: 10.5603/fm.a2017.0040
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between selected parameters of a cephalometric analysis determining the vertical morphology of facial skeleton and bite force

Abstract: Among the selected parameters determining the vertical craniofacial structure, the rear height of the alveolar process (ms-NL) exerts the greatest influence on bite force in both patients with increased and normal vertical relation of bases of jaws and skull, and with an increase in the value of ms-NL, bite force is reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Using a similar method, Szymańska and Sidoro wicz [16,21] evaluated the relationship between bite force and facial skeleton morphology. They found a significant relationship between bite force and the posterior height of the maxilla alveolar process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a similar method, Szymańska and Sidoro wicz [16,21] evaluated the relationship between bite force and facial skeleton morphology. They found a significant relationship between bite force and the posterior height of the maxilla alveolar process.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum bite force is one of the most important indicators of the functional situation of the masticatory system and its value is used to diagnose disorders of the musculoskeletal system of facial skeleton [20]. Maximum bite force is affected by skeletal craniofacial morphology, depending on the posterior/ anterior facial height ratio, vertical facial relationships, mandibular inclination and gonial angle [16,21,22]. Malocclusions are commonly associated with reduced maximum bite force.…”
Section: Resultsmentioning
confidence: 99%
“…Facial skeletal biotype is related to the growth of the mandible. Researches 22 have shown relationships between facial skeletal characteristics and multiple factors like occlusal forces, morphology of masticatory muscles and shape of mandible. Due to short mandibular ramus in high-angle patients, the maxillary plane will rotate and a compensatory dentoalveolar mechanism will be induced 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that patients with different vertical skeletal growth pattern produce different forces during swallowing, chewing and maximum bite force [3,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%